2019
DOI: 10.1136/jnnp-2019-321790
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and immunopathological analysis of CHCHD10 in Australian amyotrophic lateral sclerosis and frontotemporal dementia and transgenic TDP-43 mice

Abstract: ObjectiveSince the first report of CHCHD10 gene mutations in amyotrophiclateral sclerosis (ALS)/frontotemporaldementia (FTD) patients, genetic variation in CHCHD10 has been inconsistently linked to disease. A pathological assessment of the CHCHD10 protein in patient neuronal tissue also remains to be reported. We sought to characterise the genetic and pathological contribution of CHCHD10 to ALS/FTD in Australia.MethodsWhole-exome and whole-genome sequencing data from 81 familial and 635 sporadic ALS, and 108 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…While mutations in Coiled‐Coil‐Helix‐Coiled‐Coil‐Helix Domain Containing 10 (CHCHD10) were not found to be common, reduced expression of CHCHD10 within neurons may have a role in the pathogenesis of sporadic ALS. 37 A genome‐wide gene expression study utilising brain materials from 113 individuals with a neurodegenerative condition did not identify commonly dysregulated genes suggesting mechanistically diverse pathogenesis. 39 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While mutations in Coiled‐Coil‐Helix‐Coiled‐Coil‐Helix Domain Containing 10 (CHCHD10) were not found to be common, reduced expression of CHCHD10 within neurons may have a role in the pathogenesis of sporadic ALS. 37 A genome‐wide gene expression study utilising brain materials from 113 individuals with a neurodegenerative condition did not identify commonly dysregulated genes suggesting mechanistically diverse pathogenesis. 39 …”
Section: Resultsmentioning
confidence: 99%
“…Neuropathological materials were used to confirm that several rare mutations including TANK‐binding kinase 1 (TBK1), 38 Profilin 1 (PNF1) 62,63 and Ataxin‐2 (ATXN2) 64 are neuropathologically associated with TDP‐43. While mutations in Coiled‐Coil‐Helix‐Coiled‐Coil‐Helix Domain Containing 10 (CHCHD10) were not found to be common, reduced expression of CHCHD10 within neurons may have a role in the pathogenesis of sporadic ALS 37 . A genome‐wide gene expression study utilising brain materials from 113 individuals with a neurodegenerative condition did not identify commonly dysregulated genes suggesting mechanistically diverse pathogenesis 39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has indicated that CHCHD10 most likely functions as a chaperone for protein import. CHCHD10 is implicated in neurodegenerative diseases as inducing aggregation of TDP-43 (McCann et al 2020 ), a pathological feature of several neurodegenerative diseases (Woo et al 2017 ; Neumann et al 2007 ) Moreover, amyloid-like myo-granules were formed by TDP-43 and RNA in regenerating muscle (Vogler et al 2018 ). Our results also show that CHCHD10 interacts with TDP-43 in muscle cells, suggesting the possibility that CHCHD10 may transport TDP-43 into muscle cell nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the disease-associated CHCHD10 S59L causes mitochondrial fragmentation, loss, disassembly, and expansion of mitochondrial cristae (Bannwarth et al, 2014). In contrast, CHCHD10 protein levels were significantly lower in the spinal cord of patients with ALS and the frontal cortex of patients with frontotemporal lobe dementia (FTD) (McCann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%